2011
DOI: 10.1186/1476-7120-9-34
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial volume predicts adverse cardiac and cerebrovascular events in patients with hypertrophic cardiomyopathy

Abstract: AimsTo prospectively evaluate the relationship between left atrial volume (LAV) and the risk of clinical events in patients with hypertrophic cardiomyopathy (HCM).MethodsWe enrolled a total of 141 HCM patients with sinus rhythm and normal pump function, and 102 patients (73 men; mean age, 61 ± 13 years) who met inclusion criteria were followed for 30.8 ± 10.0 months. The patients were divided into two groups with or without major adverse cardiac and cerebrovascular events (MACCE), a composite of stroke, sudden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 16 publications
0
35
0
1
Order By: Relevance
“…Approximately 20-25% of the patients with HCM will eventually develop atrial fibrillation (AF) during the clinical course of the disease, a percentage significantly larger than that of the general population [1][2][3][4][5]. AF is a major factor of morbidity and mortality in HCM, causing ischemic strokes and systemic embolisms, exacerbation of symptoms of heart failure, pulmonary congestion and edema, deterioration of the already compromised diastolic filling of the left ventricle, as well as provoking appropriate and inappropriate discharges in patients with implantable cardioverter-defibrillators (ICDs), dramatically affecting their quality of life [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20-25% of the patients with HCM will eventually develop atrial fibrillation (AF) during the clinical course of the disease, a percentage significantly larger than that of the general population [1][2][3][4][5]. AF is a major factor of morbidity and mortality in HCM, causing ischemic strokes and systemic embolisms, exacerbation of symptoms of heart failure, pulmonary congestion and edema, deterioration of the already compromised diastolic filling of the left ventricle, as well as provoking appropriate and inappropriate discharges in patients with implantable cardioverter-defibrillators (ICDs), dramatically affecting their quality of life [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is reported to occur in approximately 1% of the general population [9], but 20-30% of the HCM population [4,10,11,12,13]. Some studies suggest that AF is associated with adverse outcomes in patients with HCM and other cardiovascular diseases [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The recently reported prevalence of AF in several HCM populations ranged from 21 to 28% [1,2,3]. A previous study reported that HCM patients have a 4- to 6-fold increased risk of developing AF compared to the general population [2].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hypertrophic cardiomyopathy (HCM), atrial fibrillation (AF) is the most common clinical complication, with a prevalence exceeding 20% in recent studies [1,2,3]. For HCM patients, AF has been associated with substantial risks of heart failure-related mortalities, strokes and severe functional disabilities [4].…”
Section: Introductionmentioning
confidence: 99%